The North West dolomite aquifers, South Africa: a stalled opportunity for water security and development - Cobbing, J. (International Water Management Institute, 2018)
The karst dolomite aquifers of the North West Province in South Africa are among the most important in the nation. They serve as key water sources for municipal water supply and irrigation, and are also ecologically important in supplying springs that feed important rivers. Over-abstraction and consequent falling groundwater levels jeopardize water supply security, with increasing costs and risks to sustainable development. Better aquifer and conjunctive water management would improve water supply security and lower costs, with wider benefits to many sectors. This GRIPP Case Profile discusses these challenges and management experiences through the examples of two representative North West dolomite aquifers - the Grootfontein and Steenkoppies aquifers. These aquifers are relatively well understood hydrogeologically, and modern South African water law mandates sustainable use. Yet, underperforming collaboration between stakeholders using and managing the aquifers at various levels, and poor support from the national authority have led to an entrenched suboptimal equilibrium where stakeholders are reluctant to change behavior, despite awareness of the negative outcomes. Neither prescriptive local nor top-down organization has been effective. The synthesis argues for prioritized input from a legally mandated and capacitated convening authority (the national Department of Water and Sanitation) to catalyze and support effective local stakeholder groups and other governance initiatives. It calls for a renewed effort by this convening authority and other stakeholders, emphasizing mutually beneficial or “win-win” outcomes.